Modelling past and future land use changes and potential conflicts from mining, agriculture, and industry in the rapidly developing region of Kuantan, Malaysia - Beream Nasir, Sharun (2022)
Kuantan is emerging as a dynamically developing region supported by the megaeconomic development projects such as the East Coast Economic Development Plan in conjunction with the extension of China-Malaysia bilateral industrial parks and establishment of East Coast Rail Link (ECRL), a part of the great Belt and Road Initiative (BRI). Such a rapidly developing region requires a robust spatial analysis to understand the changing landscape pattern and its socio-environmental impacts to guide sustainable development. Addressing the lack of research focused on this key economic development region, this study aims to characterise and evaluate the historic and future projection of land use land cover (LULC) change patterns to understand the dynamics of the regional development process and to identify potential future land use conflicts. The methodology for this research includes construction of coarse-scale land cover classes by using Landsat 5 TM and Landsat 8 OLI data based on a combination of Random Forest classifier on Google Earth Engine (GEE) platform and manual refinement to construct fine-scale LULC maps by using auxiliary reference data. The produced timeseries imageries’ overall accuracy assessment scored at an average of 83%. Subsequently, to further assess and model the future LULC change pattern, the Land Change Modeler (LCM) in TerrSet was utilized by training the multilayer perceptron (MLP) neural network and using the Markov chain analysis.